Risk Factors of Pulmonary Hemorrhage in Neonate - Afreen Aijaz, Farhana Zafar, Muhammad Iqbal, Rabeaya Muzamil, Saadullah Siddique, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Pulmonary haemorrhage (PH) is a potentially fatal respiratory complication of neonates, particularly those with very low-birth-weight infants (ELBWI), who are predisposed to diseases that need invasive ventilation and critical care after birth. Clinical PH is predicted to affect 1–12 out of every 1000 live babies [1]. Pulmonary haemorrhage is a potentially fatal disease that affects 1-12/1000 live births, with rates reaching 50/1000 births [2]. Objective: To determine the frequency of factors leading to pulmonary hemorrhage in neonates. Materials And Methods: This study was conducted at Ziauddin University Hospital, Karachi, Pakistan, and the duration of this study was from June 8, 2021 to December 7, 2021. All patients who fulfilled the inclusion criteria and visited to Pediatrics Department of Ziauddin Medical University, Karachi were included in the study. Informed consent was taken from parents / guardians after explaining the procedure, risks and benefits of the study. All of the patient data obtained included demographic information, clinical aspects, and information on mothers and infants. All data obtained were put into the accompanying proforma and utilized electronically for research purposes. Results: The age of mother was 29.6±7.8 years. In distribution of gender of baby, 63 (45%) were male, 77 (55%) were female. In distribution of factors leading to pulmonary hemorrhage, hypothermia was noted in 25 (17.8%) patients, heart failure in 42 (30.0%), disseminated intravascular coagulation (DIC) 12 (8.5%), oxygen saturation index 124 (88.6%), reduced mean platelet volume 111 (79.3%), polycythemia 20 (14.3%), patent ductus arterioses 22 (15.7%), low birth weight 97 (69.3%), respiratory distress syndrome in 44 (31.4%) while surfactant therapy was noted in 15 (10.7%) patients. Conclusion: It is to be concluded that oxygen saturation index and diabetes was noted as most common neonatal and mother factors respectively which leads to pulmonary hemorrhage in neonates. More prospective and well-controlled trials are needed to validate the current findings.